“PERSPEKTIF TOKOH MUSLIM TENTANG KURIKULUM DALAM PENDIDIKAN ISLAM” (IBNU SINA, IMAM AL-GHAZALI, ABDULLAH NASHIH ULWAN, DAN ABDURRAHMAN AN-NAHLAWI) - Ayu Suraya; Iqlimatul Fajriyah; Salsa Khumairoh; Mercy Emiliah Saleh; Popi Paudah; Madian Muhammad Muchlis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the perspectives of Muslim figures on the curriculum in Islamic education, specifically Ibn Sina, Imam Al-Ghazali, Abdullah Nashih Ulwan, and Abdurrahman An-Nahlawi, as well as their relevance to the modern Islamic education curriculum. The research method employed is library research with a qualitative descriptive approach. Data were gathered from various literature sources, including books, journals, and scientific articles related to the thoughts of these Muslim scholars on Islamic education. The results indicate that all four figures emphasize a balance between religious and general sciences, moral cultivation, and the comprehensive development of learners' potential. Ibn Sina highlights a curriculum based on the developmental stages of age and the child's potential. Imam Al-Ghazali focuses on the integration of religious and rational sciences to foster morality and spirituality. Abdullah Nashih Ulwan emphasizes character education through the family, school, and community. Meanwhile, Abdurrahman An-Nahlawi emphasizes education based on divine (rabbaniyah) values and the gradual development of human nature (fitrah). The thoughts of these scholars remain highly relevant to the modern Islamic education curriculum as they support a holistic, humanistic, and Islamic character-oriented approach to education.